Exploring Feasibility and Scope for Wind Resource Potential with Turbine Selection for a Land Site - Bansal, Ramesh Chander; Bharadwaj, Alok Kumar (Asian Journal of Electrical Sciences, 2018)
The paper presents a synthesized approach by developing a ranking criteria for deciding a wind farm location based on wind potential, site consideration factors interfaced to matching turbine design characteristics with wind properties such as its power density, cut in speed, sustainable pattern counts of air distributions and prioritized selection factors based on literature, technical expertise derived from wind manufacturers and experience of wind farm developers so as to achieve enhanced capacity factor with reduced risk of investment of the customer on a long way without suffering the surroundings and environment. For efficiency, safety, and optimized production with higher degree of reliability; concepts of variable speed turbine with basic automation is covered. Based on yearly, “metrological data” in coordination with “wind resource data” using statistical tools for deciding firm probability of average and peak wind cut in speed, frequency of occurrence of wind distributions with power density, geographical location over land nature such as terrain, off shore or on shore locations taking a feasible hub height and a economical criteria the turbine size decision; is concluded. After selecting a wind turbine, its performance data based on turbine selection factors and wind potential for the site under consideration are simulated and projected to assess its financial impact on wind farm operation and likely benefits. Measures for capacity Factor enhancement concepts are presented for higher wind energy conversion and economy.